The Principles of Welfare and Justice in Land Registration Regulations - Heru Yudi Kurniawan; Mikrot Siregar; Fidelis Harefa; Ganesh Deo Gangga; Giao Cong Vu (Journal of Human Rights, Culture and Legal System, 2026)
Indonesia's land registration system, which adopts a negative publication system with positive elements, has not fully ensured legal certainty, justice, and public welfare because land certificates may still be annulled through court decisions. This study aims to analyze the deficit of welfare and justice values in Indonesia's land registration regulations, examine the principles of the positive publication system implemented in Germany, Switzerland, and England, and formulate an appropriate regulatory reform model for Indonesia. This research employs a normative legal method using statutory, comparative, and conceptual approaches. The findings reveal that, first, Indonesia's current land registration system has not optimally guaranteed legal certainty, justice, and welfare because land certificates remain subject to cancellation. Second, the positive publication systems in Germany, Switzerland, and England provide stronger legal protection through rigorous verification procedures, state guarantees of registered data, and compensation mechanisms for administrative errors. Third, Indonesia should reform its land registration system by adopting a positive publication system through strengthening the legal framework, improving verification procedures, digitalizing land administration, and reinforcing state responsibility. These reforms are expected to enhance legal certainty, reduce land disputes, and promote justice and public welfare.